Las TICs como factor de inclusión social: Programa aplicado en Galicia, Espa\~na - Manoel Ba\~na Castro; Isabel Novo Cortí; Beatríz López González (Colegio de Economistas de A Coru\~na, 2010)
– At the same time that researching on social inclusion and collectives in social exclusion risk is going forward, the role played by families becomes more and more important for its social inclusion and future life. The collective of people with disabilities claims the correct working of their reference groups. They need them at school level, al social inclusion level, and quality of life level. Because they are the most important ones for the support asked and needed for disabled people for their process of learning and developing. In this work we show a project of harmonized development of family's supports for disabled people through ICTs applied with the accurate methodological and monitoring methods, in an environment harmonized with school experiences. In this way is boosted an multiplier effect in achieved targets for disabled collectives, so it makes easier the achievement of social inclusion and getting a quality of life level according to a developed society, that tries to maximize social welfare. This project has been developed in Galicia (Spain), through monitoring some disabled people's families, given them the means and knowledge that the families need to get ITCs at they daily routine. First results are hopeful and are stimulating to continue on this work line.
Keywords: I10; I20; I30; H51; H52; 330; TIC's (Tecnologías de la Información y Comunicación); Inclusión Social; Bienestar; Exclusión; Paradigma de Apoyos; Familias con personas de Diversidad funcional; Calidad de vida; ITCs Technologies of Information and Communication; Social Inclusion; Exclusion; Welfare; Paradigm Supports; Families with people of Functional Diversity; Quality of Life